A new frog of the genus Aromobates (Anura, Dendrobatidae) from Sierra de Perijá, Venezuela - Rojas-Runjaic, Fernando J. M.; Infante-Rivero, Edwin E.; Barrio-Amorós, César L. (Zootaxa, 2011)
A new species of diurnal frog of the genus Aromobates is described from the Sierra de Perijá in the Andes of western Venezuela. The new species is the first dendrobatid reported from this mountain range, though many other congeners are known from the Cordillera de Mérida, also in the Venezuelan Andes. It can be readily distinguished from all congeners by the unique combination of the following characters: dorsal skin granulate, paired and protuberant dorsal digital scutes, finger I shorter than finger II, fringes absent on fingers I and IV, present and conspicuous on all toes, toe webbing basal, dorsolateral stripe present, oblique lateral stripe diffuse, ventrolateral stripe absent. With this new species the number of Aromobates species from Venezuela increases to 13.